α-decay spectroscopy of the chain 179Tlg→175Aug→171Irg→167Rem - Andreyev, Andrei; Liberati, V.; Antalic, S.; Ackermann, D.; Barzakh, A.; Bree, N.; Cocolios, T. E.; Diriken, J.; Elseviers, J.; Fedorov, D.; Fedosseev, V. N.; Fink, Daniel; et al. (Physical review. C, Nuclear physics, 2013)
Detailed α-decay studies of 179Tlg and its daughter products 175Aug and 171Irg were carried out in two complementary experiments at the mass separator ISOLDE (CERN) and velocity filter SHIP (GSI). First unambiguous determination of the α-decay properties of 175Aug was performed as follows: Eα = 6433(4) keV, T1/2 = 207(7) ms, and α-decay branching ratio 90(7)%. First determination of the α-decay branching ratios for 179Tlg and 171Irg was also made: bα(179Tlg) = 60(2)% and bα(171Irg) = 15(2)%. The spins of the ground states in 175Au and 171Ir are established as 1/2+.
Im Titel sind die Zahlen "179", "175", "171" und "167" hochgestellt
Im Titel sind die Buchstaben "g" und "m" hochgestellt
Gesehen am 25.11.2020